PENGARUH PERUBAHAN ASUPAN PAKAN TERHADAP KADAR NATRIUM DARAH PADA KAMBING KACANG JANTAN - , AGUS SULISTYONO; , Dr. drh. Irkham Widiyono ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The study was aimed evaluabe the effect of feed consumption on serum natrium concentration in Kacang Goat. Four male Kacang goats aged about of one year were use in study. Goats kept on individual eage. In the first period (fullfeeding) the animals have feed adlibitum for 36 days, second period (restriction) that reducing volume of feed until 50% dry matter on the first period/32 days, and third period (refeeding) that feeding back to adlibitum/30 days. Blood sampling was taken at the end of the period before the animals were given feed in the morning. Serum natrium concentration was determined using ion selective method. The results of study showed average goat blood natrium levels in the first period was 142.75±0.83 mmol/L, and then decreased in second period 141.25±2.68 mmol/L, and increased again in third period 141.50± 1.12 mmol/L. Based on statistical analysis that there were changing of natrium concentration no significant in all periods. Could be concluded that the serum natrium levels of Kacang goat. Was not significantly changed as they feed consumption restricted up to the level 50%